Drifter: An Exploration into a Classical Criminological Construct - Vaughn, Michael G. (American journal of criminal justice, 2015)
Multiple criminological perspectives have focused on drifters—individuals who travel about without concrete plans for housing or gainful employment. Drawing on data from the National Epidemiologic Survey on Alcohol and Related Conditions (NESARC), the current study provides a large-scale epidemiological investigation of drifters. Logistic regression and latent class analyses revealed evidence of 1) normative, 2) psychologically distressed, and 3) comorbid antisocial drifters. Normative drifters differ from the general population by their alcohol and drug abuse and somewhat elevated antisocial behavior. Psychologically distressed drifters were predominately female, involved in domestic violence, were at highest odds of being diagnosed with a mental health disorder, and were characterized by poor health and disability. Finally, comorbid antisocial drifters were substantially more likely to be engaged in all forms of violent and non-violent antisocial behavior, substance abuse, and were the most dangerous. Implications for theory and research are discussed.